The Influence of Art on the Younger Generation by the Example of Junior Schoolchildren - Abitkhan Sabitkhanovich Shakirov (Zien Journals, 2023)
The article examines the influence of art on the younger generation using the example of elementary school students
Keywords: Institutional approach; inadequate perception; individuality; falsehood